Understanding the supramolecular structures and pasting features of adlay seed starches. (October 2018) - Miao, Lange; Zhao, Siming; Zhang, Binjia; Tan, Manman; Niu, Meng; Jia, Caihua; Huang, Qilin
Abstract: This work concerns the multi-scale supramolecular structures and physicochemical properties of two small adlay seed starches (Q-2 and P-6) and a big adlay seed starch (BW). Among the three starches, P-6 exhibited unique hierarchical structures and thus thermal and pasting properties. The underlying mechanism on starch property differences was discussed from a hierarchical (multi-scale) structural view. Specifically, P-6 possessed the lowest granule size, the intermediate lamellar thickness and compactness, and the highest contents of helices and crystallites with a relatively high flaw degree. These multi-scale structures were most susceptible to hydrothermal effects, eventually showing the lowest thermal transition and pasting temperatures. Also, this sample had the highest paste viscosities related to the swelling degree of starch granules and the water-holding ability of starch molecules. The shell of the fully swelled granules (granule ghosts) for P-6 were most robust under shearing and heating, resulting in the lowest breakdown viscosity ( i.e., the highest paste stability during heating). The strongest assembly capacity for the starch chains of P-6, as indicated by its highest content of orders in untreated granules, induced a prominent increase in the paste viscosity during cooling. The results here indicate that P-6 may serve as functional agents such as thickeners with low pasting temperature as well as high viscosity and high paste stability under shearing and heating. Graphical abstract: Image 1 Highlights: Pasting features of adlay seed starches were understood from a multi-scale structural view. P-6 sample had the lowest pasting and thermal transition temperatures. P-6 sample showed the highest paste viscosity throughout the pasting course. P-6 sample exhibited highest paste stability under shearing and heating conditions. A structure-property relationship was established for the adlay seed starches.